PREPARATION OFPOLYURETHANE MICROCAPSULE USING 1,3 PROPANEDIOLAS THE POLYOL COMPONENT. - Ahmad Randy; Dewi Sondari; Evi Triwulandari; Murni Handayani (Center for Science & Technology of Advanced Materials - National Nuclear Energy Agency, 2010)
PREPARATION OFPOLYURETHANE MICROCAPSULE USING 1,3 PROPANEDIOLAS THE POLYOL COMPONENT. Self-healing property is the ability of a material to heal damages automatically and autonomously. Its application would be ranged from paint coating, anti corrosion coating, space-shuttle material, construction (concrete) and automotive. Extrinsic self healing requires self healing agent preembedded or incorporated into polymer matrix that would be released and close the damage in the polymer system, where the polymer itself is not healable. Healing agents are encapsulated or embedded into the material prior application. Example of monomer encapsulated to give self healing property is isophorone diisocyanate (IPDI) encapsulated in polyurethane shell. In this study, we studied the possibility of 1,3 propanediol, that can be derived from palm oil as polyol monomer for polyurethane microcapsule shell containing IPDI or stannous octoate as a self healing agent. Microcapsule in this study was prepared by interfacial polymerization technique to form IPDI monomer in polyurethane shell. FT-IR analysis show that polyurethane prepolymer produced still have unreacted isocyanate group necessary for interfacial polymerization of polyurethane. Morphological analyses of the microcapsule products show that the products have spherical shapes with smooth surface and some with wrinkled surface. The particle sizes were ranged from 40.29 to 526.80 μm.